TRANSFORMASI MANAJEMEN SEKOLAH DIGITAL DAN PEMBELAJARAN AUGMENTED REALITY UNTUK MENINGKATKAN KUALITAS PEMBELAJARAN DI SMAS KARSIA MANADO: TRANSFORMATION OF DIGITAL SCHOOL MANAGEMENT AND AUGMENTED REALITY LEARNING TO IMPROVE THE QUALITY OF LEARNING AT SMAS KARSIA MANADO - supriyanto Supriyanto; Gaby Dainty Julliet Roring; Arif Sobirin Wibowo; Pebisitona Mesajaya Purba; Andi Waranei Ombuh (LPPM Universitas Abdurrab, 2025)
Community service carried out at Karsia Manado Private High School (SMAS) aims to improve the quality of education through digital transformation and the application of Augmented Reality (AR) technology. This program focuses on two main aspects: improving teachers' competence in using technology for learning, and implementing a school website that is integrated with the administration and online learning systems. Through training and mentoring, teachers are empowered to create more interactive and effective AR-based learning content, as well as utilize the school website to expand access to learning materials outside of school hours. The results of this program show an increase in teachers' understanding of technology and a more flexible learning process for students. The sustainability of the program is maintained through the development of guide modules that can be used by teachers as a permanent reference, as well as ongoing mentoring to ensure the optimal use of technology. This program contributes to the achievement of sustainable development goals (SDGs), particularly in improving the quality of inclusive and equitable education in North Sulawesi, especially at SMAS Karsia.